Knowledge & Practice of Nursing Ethics and Laws - Shrestha, S; Jose, P (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Nurses are responsible for the well-being and quality of life of many people, and therefore must meet high standards of technical and ethical competence. Values are the belief and attitude that influence individual behavior and process of decision making. Personal values are what nurses hold significant and true for themselves, while professional ethics involve principles that have universal applications and standards of conduct that must be upheld in all situations. From the previous study it was found that most of the nurses have the knowledge regarding nursing ethic and law but have lack of practice. MATERIAL AND METHODS: A descriptive cross sectional study was conducted among the selected nurses of Universal College of Medical Sciences and Teaching Hospital (UCMS TH) Bhairahawa Nepal. Population for the study was selected on random basis and total sample size was 60. A self-administered structured questionnaire about knowledge of nursing ethics and law was devised, tested and distributed to the nurses and practice of same sample was assessed through checklist by observing the activities of nurses by the researcher herself. RESULTS: Among the total 60 respondents only 45% had adequate knowledge of ethics and rest of them had inadequate knowledge regarding nursing ethics whereas most of the respondents i.e. 53% had adequate knowledge of nursing law and only 46% had inadequate knowledge of it. On the other hand half of the respondents do practice on nursing ethics and law and another half do less practice. As a whole it has been identified that respondents had more knowledge of nursing law than that of nursing ethics and half of them do practice on it. CONCLUSION: Findings of the study showed that knowledge of law was greater than knowledge of ethics. Overall they had no satisfactory knowledge of ethics and law. Whereas 50% of respondents does adequate practice. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11825 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 30-33